USAGE OF INTERACTIVE VIRTUAL REALITY TECHNOLOGY IN PRE-CLINICAL MEDICAL CURRICULUM DELIVERY - Chakravarthi, Srikumar; Choy, Chan; Veerakumarasivam, Abhimanyu (PEOPLE: International Journal of Social Sciences, 2017)
Teaching pathology in graduate entry medical education is predominantly through didactic lectures. Other innovative forms of imparting pathology education, such as learning through virtual microscopy, is necessary in the advancing trend of the medical curriculum. With increasing number of disease processes, some medical universities are now using more state-of-the-art technology driven software. The ultimate goal of the study was to provide options for students and teachers to use virtual microscope learning modules corresponding to key topics in pathology. Through the pathology sessions in years 1 and 2 in the graduate entry medical curriculum, we developed a series of virtual microscopy sessions. A total of nine pre-clinical modules consisting of 224 respondents were done. The students were invited to take part in an evaluation exercise consisting of basic survey questions. The anonymous data were analyzed qualitatively. A significant number of students responded positively for three important themes: (1) the virtual microscope sessions positively influenced more enthusiasm in learning pathology (84%), (2) both VM and a clinicopathological discussion in the form of case study were necessary to achieve those skills (76%), and (3) the VM sessions led to a sense of personal development as a student (71%). An interactive discussion with the students revealed that they were interested and quite enthusiastic to gain knowledge by this module, which depicted the picture, gross & microscopic with some salient text notes, and they felt that this would also be useful for them in tackling the exams, and in future, during their clinical exposure.